MRI features of pseudoangiomatous stromal hyperplasia with histopathological correlation. Issue 3 (4th January 2021) - Nia, Emily S.; Adrada, Beatriz E.; Whitman, Gary J.; Candelaria, Rosalind P.; Krishnamurthy, Savitri; Bassett, Roland L.; M. Arribas, Elsa
Abstract: Pseudoangiomatous stromal hyperplasia (PASH), a rare, noncancerous lesion, is often an incidental finding on magnetic resonance imaging (MRI)‐guided biopsy analysis of other breast lesions. We sought to describe the characteristics of PASH on MRI and identify the extent to which these characteristics are correlated with the amount of PASH in the pathology specimens. We identified 69 patients who underwent MRI‐guided biopsies yielding a final pathological diagnosis of PASH between 2008 and 2015. We analyzed pre‐biopsy MRI scans to document the appearance of the lesions of interest. All biopsy samples were classified as having ≤50% PASH or ≥51% PASH present on the pathological specimen. On MRI, 9 lesions (13%) appeared as foci, 19 (28%) appeared as masses with either washout or persistent kinetics, and 41 (59%) appeared as regions of nonmass enhancement. Of this latter group, 33 lesions (80%) showed persistent kinetic features. Masses, foci, and regions of nonmass enhancement did not significantly correlate with the percentage of PASH present in the biopsy specimens ( P  ≥ .05). Our findings suggest that PASH has a wide‐ranging appearance on MRI but most commonly appears as a region of nonmass enhancement with persistent kinetic features. Our finding that most specimens had ≤50% PASH supports the notion that PASH is usually an incidental finding. We did not identify a definitive imaging characteristic that reliably identifies PASH.